Association of passive smoking and lung cancer: Is there substantial evidence to prove the causation? - Ambati, Sudhir Kumar (International Journal Of Community Medicine And Public Health, 2021)
Cigarette smoking plays a crucial role in the development of lung cancer. Tobacco smoke positively influences lung cancer development in both smokers and never or non-smokers. The influence of passive smoke on lung cancer development is associated with toxic substances that cause chronic inflammation in the respiratory systems. Frequent or high exposure to second-hand or environmental tobacco smoke causes respiratory infections that impair lung function and triggers lung cancer development through cell damage, mitosis, and apoptosis. The toxic substances found in second-hand smoke, including carcinogens, ammonia, carbon monoxide, and nitrosamines, have a significant association with squamous cell carcinoma, small cell lung carcinoma, large cell carcinoma, and adenocarcinoma. Although some previously conducted studies showed no significant association between passive smoking and lung cancer, recent studies provide substantial evidence between their associations. Thus, exposure to passive smoke increases the risks of lung cancer.